Mobile radiation dosimeter for monitoring of total radiation on-board of civilian aircraft. (7th June 2019) - Elin, Vladimir; Sharts, Olga; Merkin, Michail
This paper describes a novel radiation dosimeter technology 'DO-RA' and its uses in commercial flights as 'DO-RA.AVIA' semiconductor module incorporated into smartphones and other electronic devices. We discuss issues of radiation exposure during flights, including possible health risks, and provide an example of experimental data regarding radiation exposure during particular flight, taken recently during 2-hour flights within Russia and in France, which can open reader's eyes to the potential impact of ionising radiation that occurs during the air flights. The article describes 'DO-RA' radiation measurement technology features and functions, demonstrates uses of 'DO-RA.AVIA' radiation measurement module for use in-flight of commercial aircraft. The article suggests more features and uses of 'DO-RA' technology for drug-discovery in-house use, outdoor applications, surveillance and as a gadget for automobiles' gadget.